Upaya Peningkatan Intoleransi Aktivitas Pada Pasien Stroke - Sa'adah, Elviatus, Wachidah Yuniartika, S.Kep., Ns., M.Kep (2017)
Stroke is a brain functional disturbance and global focal sudden and acute underway more thand 24 haours due to interruption of cerebral blood flow stroke in general can lead to disability and the problem in the world. Pressure sores and contractures is a comlication that can occur in patients stroke. Exerxise Range Of Motion (ROM) in one of rehabilitation programs. The author's purpose is apply the action Range Of Motion (ROM) in increasing intolerance activities in Ny. S stroke, the author was able to perform the assesment at Ny. S with post stroke, the author was able to compile intervention in Ny. S with post stroke. The author was able to perform implementations Ny. S with post stroke, the author wad able to do an evaluation Ny. S with post stroke. Descriptive method that the fact-finding correct interpretation, the method for the imagination of the situation on patients and collecting and truthfully, through case is studied. This case study using the method nursing proses and then of data collection observation, interview the patient and family, and an interview with the midwife. Results after taught Range of Motion (ROM) passive in stroke patients showed that no increase of exercise Range of Motion (ROM) of the motor skills of stroke patients, data in ROM exercises get before that examination of muscle-strength in the upper extremities get the results right section 5 (+), the upper limb portion left 3 (-), lower limb right section 5 (+) exstremity left section 3 (-). The results showed there is an increase in musclestrength in the left upper limb, with the results of the examination of musclestrength the results indicate the right side of the upper extremity 5 (+), the upper limb left part 4 (-), lower limb parts right 5 (+), lower extremity left section 3 (-). conclusion the data shows that workouts Range of Motion (ROM) is active can improve Range of Motion in the elbow stroke patients. This study is recomended to do further research using this type of exercise others to improve movement in stroke patients vulnerable.